We've been here all along : Wisconsin's early gay history - Wagner, R. Richard (Sociologist) (Wisconsin Historical Society Press, 2019)
"The first of two groundbreaking volumes on gay history in Wisconsin. We've Been Here All Along provides an illuminating and nuanced picture of Wisconsin's gay history from the reporting on the Oscar Wilde trials of 1895 to the landmark Stonewall Riots of 1969. Throughout these decades, gay Wisconsinites developed identities, created support networks, and found ways to thrive in their communities despite various forms of suppression--from the anti-vice crusades of the early twentieth century to the post-war labeling of homosexuality as an illness to the Lavender Scare of the 1950s. In We've Been Here All Along, R. Richard Wagner draws on historical research and materials from his own extensive archive to uncover previously hidden stories of gay Wisconsinites. This book honors their legacy and confirms that they have been foundational to the development and evolution of the state since its earliest days"--